PENGARUH PEMBERIAN AIR REBUSAN JAHE DAN DAUN MINT TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER 1 DI PUSKESMAS PASIRKUDA KABUPATEN CIANJUR - Winda Nurmanasari; Salfia Darmi; Agustina Sari; Mirnawati; Rosa; Dida Parida; Helfrida Jelani Edor; Mirnawati Mirnawati; Rosa Rosa (Bajang Institute, 2026)
Emesis gravidarum is a common complaint of nausea and vomiting experienced by pregnant women in the first trimester due to increased estrogen and hCG hormone levels. If left untreated, this condition can cause dehydration, electrolyte imbalance, weight loss, and decreased maternal well-being. A non-pharmacological effort that can be applied to reduce these symptoms is the administration of ginger (Zingiber officinale) and mint leaf (Mentha piperita) boiled water, both known to have natural antiemetic effects. This study used a quasi-experimental design with a pretest–posttest with control group design. The population consisted of first-trimester pregnant women experiencing emesis gravidarum in the working area of Pasirkuda Health Center, Cianjur Regency. A total of 56 respondents were divided into two treatment groups: one received ginger boiled water, and the other received mint leaf boiled water. The intervention was administered twice daily for seven consecutive days. The level of emesis gravidarum was measured using the PUQE (Pregnancy-Unique Quantification of Emesis and Nausea) scale before and after the intervention. Data were analyzed using the Paired Sample t-Test to determine within-group differences and the Independent Sample t-Test to compare effectiveness between groups. The results showed a significant difference in emesis gravidarum levels before and after the intervention in both groups (p = 0.024, p < 0.05). The reduction in PUQE scores was greater in the mint leaf group than in the ginger group, indicating that mint was more effective in reducing nausea and vomiting among first-trimester pregnant women. Suggestion Pregnant women are advised to consume mint leaf boiled water regularly as a natural way to reduce nausea and vomiting, accompanied by maintaining a balanced diet, adequate rest, and sufficient fluid intake during pregnancy.